Kristen mission og kvinders øgede mulighedsrum - Henningsen, Anne Folke (Kvinder, Køn & Forskning, 2005)
The article has a double objective: to emphasize the diversity of the roles and career opportunities that foreign missionary activities could provide for female missionaries, and to show how converts spawned by these missionary endeavours used their new religious affiliation and faith to actively change their worldly positions and possibilities. The analyses are based on published and unpublished material from the tiny Scandinavian mission society ‘Den Frie Østafrikanske Mission’, that worked in Natal and Zululand in present day South Africa from 1889-1899.